Tożsamość publicysty - ślady mizantropii w "Dziennikach" Stefana Kisielewskiego = Identity of a columnist: the traces of misanthropy in Stefan Kisielewski`s "Diaries" - Malon, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article deals with the notion of the columnist`s identity and its linguistic image contained in Stefan Kisielewski`s "Dzienniki" (Journals). The analysis of linguistic patterns included in the examined texts has shown an image of the columnist as a misanthropist, bitter, alienated, full of aversion to the world around and even himself, a commentator and critic.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie